About an irritating debate among northern anthropologists: Comments to the article by O. Starn - Ansión, Juan (1992)
Orin Starn's article, read from Peru, puzzles and irritates. Those of us who work from the social sciences to understand a country as complex as Peru and, at the same time, continue to bet on making it a viable country, have the right to ask ourselves about what motivates such harsh criticism of one of the best works that American anthropology has produced about a people of the Andes. We understand that, by focusing on Billie Jean Isbell's book, the author seeks to hit one of the most influential works of mountaineering, a current that is the final object of his criticism.